Odpowiedzi

2009-10-03T13:46:04+02:00
2009-10-03T13:52:41+02:00
D) -2/5(ułamek) (3-2x) =0.1 (4x+1)
-2/5*3-2x=0.1*4x+1
-6/5-2x=0.4x+1
1 1/5 -2x=0.4x+1
-2x-0.4x=1-1 1/5
1.6x=-1.5/:1.6
x=0.9375






Najlepsza Odpowiedź!
2009-10-03T13:57:27+02:00
D) -2/5(ułamek) (3-2x) =0.1 (4x+1)
-0,4 razy (3-2x) = 0,4x + 0,1
-1,2 + 0,8 = 0,4x + 0,1
-0,4x = 0,1 + 1,2 - 0,8
-0.4x = 0,5 /-0,4
x = -1,25

i) x/4=3/5 obie strony mnożymy przez4
x/4 razy 4 = 3/5 razy 4
x = 12/5
x = 2 całe i 2/5

l) x+3/3 =x/2
x+1 =x/2 obie strony mnożymy razy 2
2x +1 razy 2 = 2 razy x/2
2x + 2 = x
2x - x = -2
x = -2